1997
DOI: 10.1097/00000542-199703000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Remifentanil and Fentanyl in Patients Undergoing Craniotomy for Supratentorial Space-occupying Lesions

Abstract: Remifentanil appears to be a reasonable alternative to fentanyl during elective supratentorial craniotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(68 citation statements)
references
References 18 publications
1
66
0
1
Order By: Relevance
“…The infusion rates of propofol and remifentanil used in this study were those normally used for maintenance of anesthesia and showed efficacy and safety as previously described. 12,14,15,16 In conclusion, the present study showed that remifentanil combined with propofol in a propofol-TIVA, was interesting in reducing middle ear blood flow and providing good surgical conditions in terms of quality of operative field and provided convenient induced hypotension for tympanoplasty with no need for additional use of a potent hypotensive agent.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…The infusion rates of propofol and remifentanil used in this study were those normally used for maintenance of anesthesia and showed efficacy and safety as previously described. 12,14,15,16 In conclusion, the present study showed that remifentanil combined with propofol in a propofol-TIVA, was interesting in reducing middle ear blood flow and providing good surgical conditions in terms of quality of operative field and provided convenient induced hypotension for tympanoplasty with no need for additional use of a potent hypotensive agent.…”
Section: Discussionmentioning
confidence: 58%
“…Compared with other comparable drugs such as fentanyl 1 2 or alfentanil, [13][14][15] remifentanil appears to offer a superior intraoperative hemodynamic stability during stressful surgical events and maintains intact cerebral blood flow reactivity. 12,16 Meanwhile, it appears to provoke moderate to mild hypotension. 15,17 Since we replaced alfentanil by remifentanil in our clinical practice, we noted that this side effect led us to stop the use of nitroprusside, or esmolol for controlled hypotension.…”
mentioning
confidence: 99%
“…In recent years, remifentanil as a short acting opioid receptor agonist has been used for this purpose in order for a mild to moderate reduction of blood pressure and as an effective agent for controlled hypotension [12] . Nevertheless, high doses of remifentanil during surgery have its limits, with pain management after surgery and hyperalgesia in these patients [13] . Currently, remifentanil with propofol is used for total intravenous anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…This result contrasted with the results we obtained in our previous study with supratentorial craniotomy. 6 Guy et al 3 were the first to publish a study comparing remifentanil and fentanyl for intracranial surgery, and they found that systolic blood pressure (SBP) was greater in the remifentanil group than in the fentanyl group in the postoperative period, but transitional analgesia was not used in the remifentanil group. In our study, five patients in the block group received antihypertensive drugs, but only in the PACU; whereas in the morphine group, two patients received antihypertensive drugs in the operating room and four in the PACU.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] With the rapid metabolism of this agent, the patient may experience significant pain on awakening and a higher incidence of early postoperative hypertension. 3,4 Hence the need for a transitional method of analgesia in order to ensure a smooth and pain-free emergence from general anesthesia.…”
Section: Résumémentioning
confidence: 99%